Possible mechanisms of co-seismic electromagnetic effect - Surkov, V.V.; Pilipenko, V.A.; Sinha, Anup K. (My University, 2018)
We analyze theoretically two possible sources of co-seismic electromagnetic response to the propagation of various types of seismic waves caused either by the electrokinetic phenomena or geomagnetic inductive effect. The differences between these two generation mechanisms have been examined for different types of seismic waves (P, S, and Rayleigh-Love). Theoretical relationships describing the dependence of the co-seismic signal amplitude, polarization and apparent impedance on the earthquake seismic moment and magnitude have been derived as a function of distance. We indicate an observational possibility to discriminate seismo-electrokinetic and seismo-magnetic effects and to estimate their contribution into a recorded co-seismic electromagnetic signal. Magnitudes and polarization of these signals are shown to depend strongly on the type of seismic wave and local crust parameters, such as streaming potential coupling coefficient, conductivity, inhomogeneity, etc. Co-seismic electromagnetic signals, though not directly applied for earthquake prediction, contain a useful information on local crustal phenomena, and can be used to identify ‘‘sensitive’’ zones perspective for the monitoring of precursory electromagnetic disturbances.
Keywords: Geomagnetic inductive effect; Electrokinetic phenomena; Co-seismic effect; Geophysical prospecting; Earthquake